The Role of Football Supporters Attachment to The Club - Muhad Fatoni; Nur Subekti; Zandra Dwanita Widodo (JUARA : Jurnal Olahraga, 2022)
The purpose of this study was to determine the behaviour of football supporters in terms of the trust, satisfaction, commitment and loyalty factors. This research uses the descriptive quantification method. The sample in this study were football club supporters in Surakarta and Yogyakarta. Data were collected using a structured questionnaire on a Likert scale. They were testing the relationship between variables in the hypothesis using Spearman correlation. The results showed that the five variables studied had a positive correlation value, and based on the results obtained were able to confirm that the seven hypotheses proposed based on the conceptual model in the study were accepted.